2016
DOI: 10.1161/hypertensionaha.116.07901
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Patients With Hypertension

Abstract: A trial fibrillation (AF) is the commonest sustained cardiac arrhythmia, with an increasing prevalence and incidence with age and associated cardiovascular comorbidities.1 The prevalence and incidence of hypertension also increases with increasing age, and hypertension is the commonest pathogenic risk factor for the development of AF. The development of AF is most evident in the presence of hypertensive left ventricular hypertrophy, especially where there is associated heart failure with preserved ejection fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the present study, regression analysis showed that HTN was significantly correlated with HF and DM. HTN not only causes AF, but also increases the risk of AF complications, particularly HF and embolic cerebrovascular stroke 31. In this study, hypertensive patients with AF were at three times more risk of developing HF than nonhypertensive patients ( P <0.005) and four times more likely to have comorbid T2DM ( P <0.001).…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, regression analysis showed that HTN was significantly correlated with HF and DM. HTN not only causes AF, but also increases the risk of AF complications, particularly HF and embolic cerebrovascular stroke 31. In this study, hypertensive patients with AF were at three times more risk of developing HF than nonhypertensive patients ( P <0.005) and four times more likely to have comorbid T2DM ( P <0.001).…”
Section: Discussionmentioning
confidence: 54%
“…Though assessing ventricular function is essential, there is robust data that atrial function is also important and can improve our decision making by determining the risk of cardiovascular events in various conditions [ 1 ]. Hypertension is the most common predisposing factor for left ventricular (LV) diastolic dysfunction (DD), which leads to increased left atrial (LA) pressure, its enlargement and fibrosis as well as other proarrhythmic pathological effects on atrial structure and function [ 2 , 3 ]. These changes cause various cardiac arrhythmias, most commonly atrial fibrillation (AF), an arrhythmia that carries a substantial risk of embolic events.…”
Section: Introductionmentioning
confidence: 99%
“…In the heart, the impairment of cardiac structure and function is so evident that it is referred as hypertensive heart disease [26]. It includes left ventricular hypertrophy, cardiomegaly, systolic and diastolic dysfunction, and finally heart failure [9,27]. Even atrial fibrillation is said to be a certain presentation of TOD [27].…”
Section: Diagnostic Difficultiesmentioning
confidence: 99%
“…It includes left ventricular hypertrophy, cardiomegaly, systolic and diastolic dysfunction, and finally heart failure [9,27]. Even atrial fibrillation is said to be a certain presentation of TOD [27].…”
Section: Diagnostic Difficultiesmentioning
confidence: 99%